Determination of Load Performance of Two-Bar Girder Lining; E3S Web of Conferences; Vol. 15 : International Innovative Mining Symposium (in memory of Prof. Vladimir Pronoza) - Glazkov Yu. F. Yury Fedorovich; Kazantsev A. A. Anton Aleksandrovich; Nesteruk D. N. Dmitry Nikolaevich; Aksenov V. V. Vladimir Valerievich; Efremenkov А. В. Andrey Borisovich (2017, 2017)
Title screen